EFEKTIVITAS BANTUAN KEUANGAN DALAM MEWUJUDKAN KEMANDIRIAN PARTAI POLITIK DI PROVINSI JAMBI - Maratun Saadah (Universitas Halu Oleo, 2022)
This study aims to see the effectiveness of financial assistance provided to political parties in order to realize party independence in Jambi Province. The presence of political parties is a consequence of the choice of the political system and form of government adopted by a country. Political parties have a central function as components in a democratic country like Indonesia. Political party financial assistance is deemed necessary to be given to political parties to carry out their functions, so that they are independent and free from personal interests. This research is a qualitative research conducted through in-depth interviews and described descriptively. The results showed that although the organizer of the aid in this case was the national and political unitary body of the Jambi Province, it had implemented regulations in accordance with the procedures, but the distribution of financial assistance was hampered due to the presence of parties that did not follow the procedures. Collective disbursement of aid is the cause of delays in the distribution of financial aid and leads to the ineffective use of financial aid funds by political parties as an effort to realize the independence of their parties.